(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The epizootic situations of trypanosomiasis in camels and donkeys in the northern zones of the Republic of Karakalpakstan were studied, while the spread of trypanosomiasis in most farms was noted, trypanosomiasis strains were isolated and a cryopreservation was created.